2015
DOI: 10.2519/jospt.2015.5590
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Clinical Test of Thoracolumbar Dissociation in Chronic Low Back Pain

Abstract: Motor control deficits are common in chronic/recurrent low back pain (LBP) 3,13,19,24,33,34,36 and include altered paraspinal muscle function. 4,5,19,29 Recovery from LBP does not ensure restoration of spine function or movement, and recurrent LBP involves persistent alterations of motor control, including modified coordination between short/deep (eg, multifidus) and long/ superficial (eg, thoracic erector spinae) paraspinal muscles, with a tendency to contract these muscles en masse rather than to activate T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…in the NSLBP population. 28,83 A similar observation has been made in primates with focal hand dystonia, who exhibited a loss of discrete organization of finger representations in somatosensory cortices, which coincided with a reduced ability to isolate finger movements. 84 However, this hypothesis remains elusive, as we only applied proprioceptive stimuli (i.e., muscle vibration) to one lumbar level (i.e., L4-5).…”
Section: Location Of the Activation Peak During Lower Back Proprioceptive Processing In S2supporting
confidence: 61%
“…in the NSLBP population. 28,83 A similar observation has been made in primates with focal hand dystonia, who exhibited a loss of discrete organization of finger representations in somatosensory cortices, which coincided with a reduced ability to isolate finger movements. 84 However, this hypothesis remains elusive, as we only applied proprioceptive stimuli (i.e., muscle vibration) to one lumbar level (i.e., L4-5).…”
Section: Location Of the Activation Peak During Lower Back Proprioceptive Processing In S2supporting
confidence: 61%
“…Validity and reliability for the tests used in this study were established in previous research. 13,[16][17][18][21][22][23]27,40 Three participants experienced physical discomfort during testing and were excluded. As such, 139 participants were considered for statistical analysis (mean 6 SD age, 19.5 6 1.4 years).…”
Section: Resultsmentioning
confidence: 99%
“…We used a single-session intervention, which consisted of 2 Ă— 2 min of pelvic tilt exercises in the sagittal plane, with 30 s of rest in between. Pelvic tilt exercises are often used in the rehabilitation of patients with CLBP, and their purpose is to (re)gain movement control of the lumbar spine and pelvis [40,41]. The latter can be important, as it has been suggested that poor movement control may be an underlying mechanism contributing to the persistence of CLBP [42].…”
Section: Interventionmentioning
confidence: 99%